Impact of rising political risks in Asean on US multinational corporations investments. - Ryotaka Goto. (2008)
The East Asian crisis, brought about by the devaluation of the Thai Baht in July 1997, created alarm amongst investors and resulted in capital flights from the region. A key factor for recovery now is the infusion of foreign direct investment (FDI) into the current account to fuel the engine for growth. However, in the light of rising political risk in certain countries of the region, how affected will investors be by this factor in deciding on investments in the region.